Kepemimpinan Kepala Sekolah Dalam Pembinaan Kinerja Guru Di Sd Negeri Drajidan Kecamatan Musuk Kabupaten Boyolali - Astuti, Atik Puji, Drs. Saring Marsudi, SH. M.Pd (2017)
ABSTRACT This study aims to determine: 1) Types of coaching performance of teachers by principals in SD Negeri Drajidan, 2) Business (Strategy) leadership principals in coaching the performance of teachers in SD Negeri Drajidan, 3) Problems principal's leadership in fostering teacher SD Negeri Drajidan and 4) the principal's leadership efforts in addressing the issue in coaching the performance of teachers in SD Negeri Drajidan. The research is a qualitative research with qualitative descriptive design. Informants in this study are principals and teachers in public SD Negeri Drajidan. Data collection techniques uses interviews, documentation and observation. Data is analyzed through the steps of data reduction, data presentation and conclusion. Mechanical examination of the validity of data is done by using triangulation of sources and technique. The results show the types of teacher performance coaching, carried by the head of the school is the kind of coaching with the general supervision, supervision of teaching, clinical supervision and oversight attached. Enterprises principals in the implementation of teacher performance coaching that can be done well, namely with the coaching work discipline, motivation, awards, training, and supervision of teacher performance. This study therefore concluds that the development of teacher performance is conducted by the school head can work well and can improve the performance of teachers in SD Negeri Drajidan. Keywords: Leadership principals, coaching of teacher performance